Socially gainful gender quotas - Oded Stark; Walter Hyll (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
We study the impact of gender quotas on the acquisition of human capital. We assume that individuals' formation of human capital is influenced by the prospect of landing high-pay top positions, and that these positions are regulated by gender-specific quotas. In the absence of quotas, women consider their chances of getting top positions to be lower than men's. The lure of top positions induces even men of relatively low ability to engage in human capital formation, whereas women of relatively high ability do not expect to get top positions and do not therefore engage in human capital formation. Gender quotas discourage men who are less efficient in forming human capital, and encourage women who are more efficient in forming human capital. We provide a condition under which the net result of the institution of gender quotas is an increase in human capital in the economy as a whole.
urn:nbn:de:bsz:21-dspace-520596
Keywords: D01; D21; J16; J24; J70; M51; 330; Gender quotas; Affirmative action; Human capital formation